Implementasi Pendekatan Deep Learning Pada Pembelajaran Pendidikan Agama Hindu dan Budi Pekerti di SMA Dwijendra Denpasar - Ni Komang Wiwin Nurhayati; I Nyoman Alit Supandi; I Made Nasib Mardika (Scientific Journal for Nation Building, 2026)
The Importance of Implementing the Deep Learning Approach in Hindu Religious Education and Character Education at Dwijendra High School in Denpasar. This study aims to analyze the implementation of the Deep Learning approach in Hindu Religious Education and Character Education at Dwijendra High School in Denpasar, identify supporting factors and challenges encountered, and determine the impact of its implementation on students’ understanding. This study employs a qualitative approach using a descriptive phenomenological research design. Data were collected through observation, interviews, documentation, and literature review. The research informants consisted of Hindu Religious Education and Character Education teachers, students at Dwijendra High School in Denpasar, as well as the Principal or Vice Principal in charge of the curriculum. The study utilized two theories: Constructivism and Deep Learning Theory. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, with data validation achieved through triangulation of sources and techniques. The research findings indicate that the implementation of the Deep Learning Approach proceeded smoothly through the planning, implementation, and conclusion phases, supported by adequate facilities, the teacher’s role as a facilitator, and the use of a variety of interactive teaching methods. Despite facing challenges such as teacher adaptation and student perceptions, this approach has proven to have a positive impact on students’ understanding, motivation, learning outcomes, and ability to relate the material to daily life, as well as demonstrate an understanding of Hindu values. This approach is capable of creating learning that is more meaningful, joyful, and mindful.